Suppose that

 fix = λf.(λx.f (xx)) (λx.f (xx)).

Show that, for every F, fix F = F(fix F).

In each term, a redex (λv.A) B that is about to be replaced is shown with the λ in green, the function body in red and the argument in blue.

An expression that is about to be replaced with an equal expression is shown in purple.

  1. fix F

     = λf.x.f (xx)) (λx.f (xx)) F

     ⇒βx.F(xx)) (λx.F(xx))

  2. (λx.F(xx)) x.F(xx))

     ⇒β F((λx.F(xx)) (λx.F(xx)))

  3. F(x.F(xx)) (λx.F(xx)))

     = F(fix F) (by (a))